2009
DOI: 10.1111/j.1365-2125.2009.03543.x
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of capsaicin‐induced increase in dermal blood flow by the oral CGRP receptor antagonist, telcagepant (MK‐0974)

Abstract: WHAT IS ALREADY KNOWN ABOUT THIS SUBJECT• Calcitonin gene-related peptide (CGRP) was first described as a potent vasodilator.• CGRP is also increasingly recognized as a key player in the pathophysiology of migraine, and CGRP receptor antagonists potentially offer a new approach for treating migraine.• A novel pharmacodynamic assay to measure CGRP receptor antagonist activity non-invasively in humans has been developed, which involves measuring the increase in dermal blood flow induced by topical application of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
89
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 79 publications
(98 citation statements)
references
References 34 publications
(47 reference statements)
9
89
0
Order By: Relevance
“…These results indicate that a halfmaximal in vivo effect is achieved at unbound plasma concentrations that are approximately twofold in excess of the in vitro IC 50 . When similarly evaluated in humans, telcagepant reduced the capsaicin-induced effect at an IC 50 of 101 nM total or 4 nM unbound (Sinclair et al, 2010), a similar approximately 2-fold in excess of the in vitro IC 50 , supporting the clinical translatability of this pharmacodynamic model. This was also true when evaluating the nearmaximal effect in NHP relative to humans.…”
Section: Discussionmentioning
confidence: 73%
“…These results indicate that a halfmaximal in vivo effect is achieved at unbound plasma concentrations that are approximately twofold in excess of the in vitro IC 50 . When similarly evaluated in humans, telcagepant reduced the capsaicin-induced effect at an IC 50 of 101 nM total or 4 nM unbound (Sinclair et al, 2010), a similar approximately 2-fold in excess of the in vitro IC 50 , supporting the clinical translatability of this pharmacodynamic model. This was also true when evaluating the nearmaximal effect in NHP relative to humans.…”
Section: Discussionmentioning
confidence: 73%
“…In the case of CGRP 8-37 , it was suggested that this is due to its relatively lower affinity. The small molecules previously tested in this assay (MK-3207 and telcagepant) displayed higher affinity to CGRP-R than CGRP 8-37 , but still did not block the DBF response completely (Sinclair et al, 2010;Li et al, 2014). Mediators, such as nitric oxide, substance P, and prostaglandins, were previously excluded from playing a significant role in the capsaicin assay (Van der Schueren et al, 2008).…”
Section: Discussionmentioning
confidence: 92%
“…We have previously reported the inhibition of capsaicininduced DBF in the rat using LY2951742 (Benschop et al, 2014). A similar method has been used by others to assess the target engagement of small molecule inhibitors of the CGRP receptor in the periphery in both preclinical (Hershey et al, 2005;Salvatore et al, 2008) and clinical (Salvatore et al, 2010;Sinclair et al, 2010) settings. Both LSN2915644 and LY2951742 antibodies bind CGRP with high affinity (10 and 31 pM, respectively; R. J.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations